Simultaneous approximation by polynomials in Orlicz spaces generated by quasiconvex Young functions - koc, huseyin (Kuwait Journal of Science, 2016)
In this paper we prove some theorems on simultaneous approximation by trigonometric or algebraic polynomials in Orlicz spaces constructed by Young functions belonging to a reasonably wide class.